2022
DOI: 10.1186/s13018-022-03398-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of platelet-rich plasma combined with hyaluronic acid versus platelet-rich plasma alone for knee osteoarthritis: a systematic review and meta-analysis

Abstract: Purpose To systematically evaluate the curative efficacy and safety of platelet-rich plasma (PRP) combined with hyaluronic acid (HA) in the treatment of knee osteoarthritis (KOA), comparing with platelet-rich plasma alone. Methods Cochrane Library, PubMed, China National Knowledge Infrastructure (CNKI) and Embase were searched for randomized controlled trials (RCTs) and cohort studies regarding the efficacy and safety of platelet-rich plasma (PRP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…3 B). Zhang et al determined the MCID for the VAS score to be 1.16 in a systematic review [ 23 ]. The pooled results in our meta-analysis showed that the smallest improvement seen in the VAS score (− 0.36) did not exceed the MCID (1.16), indicating that although the VAS score was statistically significant, it may not have a meaningful clinical impact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 B). Zhang et al determined the MCID for the VAS score to be 1.16 in a systematic review [ 23 ]. The pooled results in our meta-analysis showed that the smallest improvement seen in the VAS score (− 0.36) did not exceed the MCID (1.16), indicating that although the VAS score was statistically significant, it may not have a meaningful clinical impact.…”
Section: Resultsmentioning
confidence: 99%
“…The VAS score was to quantitatively evaluate the pain intensity, with lower scores indicating less pain [ 29 ]. The pooled MD in the VAS score (− 0.36) was also below the MCID (1.16), suggesting that the improvement in pain intensity was not deemed to be clinically significant [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the incidence of adverse events, PRP combined with HA is usually safer than PRP injection alone. [ 22 ] In a review by Brian J. Cole, it was shown that there are various devices used to centrifuge PRP and that differences in centrifugation speed and duration result in differences in platelet and leukocyte concentrations, and it was suggested that treating the knee with leukocyte-depleted PRP early in KOA could prevent or slow the onset of advanced KOA. [ 23 ] The second-ranked author, Giuseppe Filardo, from the IRCCS Rizzoli Orthopaedic Institute in Bologna, Italy, showed in a 5-year double-blind, randomized controlled trial with Elizaveta Kon that both PRP and HA were effective in improving knee function, but follow-up failed to show that PRP had a clinical effect was better than that of HA.…”
Section: Resultsmentioning
confidence: 99%
“…These results could be explained by better inflammation downregulation, particularly on the infrapatellar fat pad and the synovial membrane [29]. Nevertheless, other meta-analyses did not prove any superiority of PRP combined with HA compared to PRP alone [30]. Cellular analyses demonstrated a twofold increase in platelet concentration.…”
Section: Discussionmentioning
confidence: 99%